A look‐locker acquisition scheme for quantitative myocardial perfusion imaging with FAIR arterial spin labeling in humans at 3 tesla. Issue 2 (8th September 2016) - Keith, Graeme A.; Rodgers, Christopher T.; Chappell, Michael A.; Robson, Matthew D.
Abstract : Purpose: A novel method for quantitative measurement of myocardial blood flow (MBF) using arterial spin labeling (ASL) in a single breath‐hold is presented, evaluated by simulations, phantom studies and in vivo studies and tested for reproducibility and variability. Methods: A flow‐sensitive alternating inversion recovery (FAIR) ASL method with Look‐Locker readout (LL‐FAIR‐ASL) was implemented at 3 tesla. Scans were performed on 10 healthy volunteers and MBF measured in three slices. The method was investigated for reproducibility by Bland‐Altman analysis and statistical measures, the coefficients of reproducibility (CR) and variation (CV) are reported. Results: The MBF values for the basal, mid, and apical slices were 1.04 ± 0.40, 1.06 ± 0.46, and 1.06 ± 0.38 ml/g/min, respectively (mean ± SD), which compare well with literature values. The CV across all scans, 43%, was greater than the between‐session and within‐session values, at 16 and 13%, respectively, for the mid‐ventricular slice. The change in MBF required for detection, from the CR, was 61% between‐session and 53% within‐session for the mid‐ventricle. Conclusion: This study shows the feasibility of the LL‐FAIR‐ASL method for the quantification of MBF. The statistical measures reported will allow the planning of future clinical research studies involving rest and stress measurements. Magn Reson Med 78:541–549, 2017. © 2016 The Authors Magnetic Resonance in Medicine published by Wiley Periodicals, Inc. on behalf of International Society for Magnetic Resonance in Medicine. This is an open access article under the terms of theCreative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.